The Contribution of Students’ Schemata on Reading Comprehension - Husain, Djamiah; Yansar, Yansar (State University of Makassar, 2022)
The objectives of this research are to describe: (1) The contribution of the content schemata of the fourth semester students of English Department of UIN Alauddin Makassar on their reading comprehension. (2) the contribution of the formal schemata of the fourth semester students of English Department of UIN Alauddin on their reading comprehension. This research applied a quantitative descriptive method. The students of the research were the fourth semester students of English Department of UIN Alauddin Makassar, academic year 2996/2007 on their reading comprehension. The data collected were the students’ schemata through questionnaires and the students’ reading comprehension through reading test. The data obtained were analyzed quantitatively using inferential statistical analysis, namely simple linear regression. The result of the data analysis showed that the coefficient determination of R square (R²) on content schemata toward reading comprehension was .761 or 76.1 percent and the coefficient of R square (R²) on formal schemata toward reading comprehension was .677 or 67.7 percent. Based on the data, the researcher concluded that there was a high contribution of the students’ content schemata toward their reading comprehension on familiar text, while on unfamiliar text, the students’ content schemata could not give any contribution to reading comprehension, and there was an average contribution of the students’ formal schemata toward their reading comprehension on familiar text, while on unfamiliar text, the students’ formal schemata could not give any contribution to reading comprehension.Keywords: Content schemata, formal schemata, reading comprehension